DEVELOPING CONTINUOUS CREATIVE THINKING IN SCHOOLCHILDREN - Kuatovna, Maksetova Nurjamal (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to examine how continuous creative thinking can be effectively nurtured in primary education by reviewing theoretical frameworks, analyzing international best practices, and evaluating ongoing reforms in Uzbekistan’s school system. Method: The research employs a qualitative analysis of educational reforms, pedagogical strategies, and pilot program outcomes, drawing from both literature and empirical evidence from schools in Tashkent. Result: The findings demonstrate that constructivist pedagogies—such as project-based learning, design thinking, reflective journals, and collaborative roles—significantly enhance students’ originality, fluency, and engagement, with a 19% increase in creative assessment scores observed in pilot schools. Novelty: This research redefines creativity as a longitudinal, iterative process rather than episodic inspiration, emphasizing the role of metacognitive strategies, sociocultural ecosystems, and structural innovations like “innovation corners” and home-school partnerships to embed continuous creativity into everyday schooling.